Incidence and Risk Factors of Major Neonatal Birth Injuries in a Tertiary Care Hospital in Thailand: A Retrospective Cohort Study - Phuengphaeng A. (2023)
Major neonatal birth injuries can cause short- and long-term negative neonatal outcomes. To date, there is still limited information on major neonatal birth injuries in Thailand, both in terms of incidence and associated factors. The objectives of this retrospective cohort study were to determine the incidence and associated factors of major neonatal birth injuries in a tertiary care hospital in Thailand. Medical records of 15,209 deliveries were reviewed and major neonatal birth injuries were identified. For each case of major neonatal birth injuries, another four controls were randomly selected as a comparison group to determine possible associated factors. A total of 81 cases with major neonatal birth injuries were identified, corresponding to incidence of 0.53%. Most common injuries were subgaleal hematoma (0.414%), fracture of clavicle (0.066%), and brachial plexus injuries (0.066%). Those with major neonatal birth injuries compared to those without injuries were significantly more likely to be nulliparous, had higher birth weight, higher rate of large for gestational age and macrosomia. They had significantly higher rate of birth asphyxia and neonatal intensive care unit admission with a longer hospital stay. Independent associated factors were abnormal second stage of labor, instrumental delivery, and large for gestational age infants. Understanding the incidence and associated factors could help raising awareness when caring women at higher risks for neonatal birth injuries. Anticipation, preparation, and early detection of the conditions would result in timely management and improvement of neonatal outcomes.